A new species of Liolaemus from the darwinii group (Iguania: Liolaemidae), Tucumán province, Argentina - Heredia, Viviana Juárez; Robles, Cecilia; Halloy, Monique (Zootaxa, 2013)
A new species of the genus Liolaemus (Iguania: Liolaemidae) is described from the province of Tucumán, northwestern Argentina. This new lizard species is a member of the L. boulengeri group and within this group, it is a member of the L. darwinii subgroup. It is found at a site called Los Cardones (Km 98), at an altitude of 2725 m, near Amaicha del Valle, Tucumán province. Including this new species, the L. darwinii subgroup now has 20 species. Liolaemus pacha sp. nov. was known as L. quilmes, but differences mainly in size (snout-vent-length and head measurements) and in color pattern show that it clearly separates from this species and others of this group. Male and female snout-vent lengths, male width, height and length of head are greater than in L. quilmes. It also exhibits a larger and wider male torso, larger hand, and a greater number of gular scales and scales around the body. Adult males of L. pacha sp. nov. present a more marked col-oration pattern, with numerous light blue and white spots, discontinuous yellow dorsolateral stripes, paravertebrals and prescapular black spot enlarged and more conspicuous than in males of L. quilmes.